Evaluation of next-generation sequencing for the pathogenic diagnosis of children brain abscesses. Issue 4 (April 2019) - Hu, Hui-li; Guo, Ling-yun; Wu, Hong-long; Feng, Wen-ya; Chen, Tian-ming; Liu, Gang
Summary: In this study, we applied metagenomic next-generation sequencing (mNGS) to detect the causative pathogens in brain abscess samples from 4 pediatric patients. NGS could offer unbiased sequencing and rapid diagnosis of causative pathogens, moreover, it could detect multiple pathogenic microorganisms from abscess samples. In our study, Fusobacterium nucleatum, and Streptococcus intermedius or combinations of them were found in 3/4 of polymicrobial brain abscesses. Internal organ abscesses are illustrative of the shortcomings of bacterial culture. NGS has the ability to identify both common and rare pathogens without any prior suspicious needed, and is able to offer a new platform for quantification of all detected microorganisms. Our study displayed the possible potential that NGS is about to provide the diagnostic tools that can characterize even the most complex microbial communities during brain abscesses and is less affected by prior antibiotic exposure.